2005
DOI: 10.1119/1.2000976
|View full text |Cite
|
Sign up to set email alerts
|

A research-based approach to improving student understanding of the vector nature of kinematical concepts

Abstract: In this paper we describe a long-term, large-scale investigation of the ability of university students to treat velocity and acceleration as vectors in one and two dimensions. Some serious conceptual and reasoning difficulties identified among introductory students also were common among pre-college teachers and physics graduate students. Insights gained from this research guided the development of instructional materials that help improve student learning at the introductory level and beyond. The results have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
2
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 22 publications
9
87
2
10
Order By: Relevance
“…This type of confusion-students interchanging average and instantaneous velocity for objects that are not experiencing constant acceleration-has been documented in the PER literature among first-semester calculus-based physics students in the context of kinematics [4,14]. The second most common incorrect response given was a ranking consistent with the value of the function at each point rather than the slope at each point.…”
Section: Difficulties In Mathematics Consistent With Physics Difficulmentioning
confidence: 98%
“…This type of confusion-students interchanging average and instantaneous velocity for objects that are not experiencing constant acceleration-has been documented in the PER literature among first-semester calculus-based physics students in the context of kinematics [4,14]. The second most common incorrect response given was a ranking consistent with the value of the function at each point rather than the slope at each point.…”
Section: Difficulties In Mathematics Consistent With Physics Difficulmentioning
confidence: 98%
“…Shaffer and McDermott [2] showed that students were better able to subtract vectors when no physical context was involved. When discussing implications for developing tutorial curricula, they cite context as being 'critically important'.…”
Section: Introductionmentioning
confidence: 99%
“…Among the primary needs of elementary and secondary teachers is foundational conceptual understanding of physics content [46][47][48]. Our conceptual learning goal is for learners to conserve energy as they track the transfers and transformations of energy within, into, or out of the system of interest in complex physical processes.…”
Section: Goals For Energy Learningmentioning
confidence: 99%